Grade 11 Public Schools Students' Knowledge and Challenges in Learning the Sociocultural History of Negros Occidental - Galvez, John Allan A.; Bual, Joel M.; Madrigal, Dennis V. (Technium Social Sciences Journal, 2025)
Understanding Culture, Society, and Politics (UCSP) plays a vital role in shaping one's cultural identity. Meanwhile, the sociocultural history of Negros Occidental holds significant importance for a deeper understanding of the region's distinct cultural and social dynamics. Thus, this study assessed the students' knowledge of the sociocultural history of Negros Occidental. Also, it identified the challenges encountered in learning the sociocultural history. Using the quantitative design, the 278 total enumeration sampled grade 11 students responded to the multiple-choice questionnaire. The data were analyzed using mean, standard deviation, and KR20. Meanwhile, the researcher adhered to the Philippine Health Research Ethics Board (PHREB). Generally, they have a low knowledge of the sociocultural history of Negros Occidental. The knowledge of social history in educational, political, familial, religion, and economics are all low. The knowledge of cultural history in values and beliefs are all low and very low in norms. In challenges, teachers find it hard to give examples of local history. Mostly, their instruction is from textbooks. Students struggle with lessons and have a weak social science foundation. In the learner environment, the school is deficient in learning materials. Also, the classroom is not conducive to learning. In subject, topics are broad. Additionally, some subject's lessons are unimportant.